A dynamic power management strategy of a grid connected hybrid generation system using wind, photovoltaic and Flywheel Energy Storage System in residential applications - Boukettaya, Ghada; Krichen, Lotfi (Energy (Oxford), 2014)
A global supervisory strategy for a micro-grid power generation system that comprises wind and photovoltaic generation subsystems, a flywheel storage system, and domestic loads connected both to the hybrid power generators and to the grid, is developed in this paper. The objectives of the supervisor control are, firstly, to satisfy in most cases the load power demand and, secondly, to check storage and grid constraints to prevent blackout, to reduce energy costs and greenhouse gas emissions, and to extend the life of the flywheel. For these purposes, the supervisor determines online the operation mode of the different generation subsystems, switching from maximum power conversion to power regulation. Decision criteria for the supervisor based on actual variables are presented. Finally, the performance of the supervisor is extensively assessed through computer simulation using a comprehensive nonlinear model of the studied system. •We supervise a micro-grid power generation system with an objective to produce clipping grid consumption.•The supervisor switch online from maximum power conversion to power regulation.•We provide services both for domestic users and for the distribution network manager.•The developed algorithm is tested and validated for different scenarios.